The built environment and public health - Lopez, Russ.; ebrary, Inc. (San Francisco : Jossey-Bass, 2012)
"This text combines an examination of how the physical environment affects our health with a description of how public health and urban planning can work together to create environments that improve human health and well-being. The author covers a wealth of topics including foundations, the joint history of public health and urban planning, transportation and land use, infrastructure and natural disasters, assessment tools, indoor air quality, water quality, food security, health disparities, mental health, social capital, and environmental justice. The Built Environment and Public Health is written for students and professionals involved in public health, urban planning, transportation, architecture, and the environment"--
pt. 1. Background and history -- pt. 2. Community design -- pt. 3. Environmental media -- pt. 4. Population health -- pt. 5. Tools and applications.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Urban health; Electronic books